How far are N-of-1 studies suitable evaluation designs in forensic psychiatric sports therapy? <subtitle>A methodological discussion</subtitle> - Vanessa Reimer; Martina Kanning (Hogrefe AG, 2024)
Abstract: Introduction: Some evidence showed positive effects of sports therapy in forensic settings. Most of these evaluation studies analyzed between-subject relations and used RCTs (randomized controlled trials) to investigate intervention effects. RCTs normally randomize participants to an intervention and a control group with the intention to compare averaged group-findings. However, such averaged results, which are based on group effects may not apply to every single forensic patient as they do not adequately address that these patients are unique due to their complex psychopathology. Thus, RCTs do not adequately address the following circumstances especially relevant in forensic settings: heterogeneity and low sample size of therapy groups and low compliance rate of forensic patients. To address these challenges, it could be worthwhile to focus on within-subject relations by using N-of-1 studies. Methods: This viewpoint summarizes the possibilities and limitations of N-of-1 study designs regarding the challenges heterogeneity, low sample size and a low compliance rate when evaluating forensic sports therapy. Results: N-of-1 studies offer a useful addition in the evaluation of sports therapy in forensic psychiatry. They are able to evaluate individual effects and they increase the power of the study by increasing the number of measurements. Nevertheless, they are associated with limitations, for example increased effort due to frequent measurements and long study duration or the difficulty to generalize the results. Conclusion: Future studies should implement N-of-1 study designs in forensic psychiatric sports therapy to gain evidence and should find solutions to deal with the limitations (e.g., digital technology).